Preferential C-nociceptor stimulation facilitates peripheral axon reflex flare, but not secondary mechanical hyperalgesia - Daneffel, Luana; Rukwied, Roman; Schmelz, Martin; Ruppen, Wilhelm; Schneider, Tobias (Frontiers in Pain Research, 2025)
“Silent” C-nociceptors are crucial for inducing the axon reflex erythema in humans and may also contribute to spinal sensitization such as secondary hyperalgesia. Electrical slow depolarizing stimulation paradigms activate unmyelinated C-fibers [25 ms half-sine (HS) profile] whereas A-fibers are stimulated by 500 µs rectangular (R) pulses. We therefore expect to provoke larger areas of axon-reflex flare (silent nociceptor activation) and secondary hyperalgesia to HS stimuli. We compared axon-reflex erythema and secondary mechanical hyperalgesia areas induced by intracutaneous electrical HS and R stimuli using stimulation intensities that induced pain ratings of 3 and 6 on a numeric rating scale (NRS 0–10) in 24 healthy volunteers. Slowly depolarizing C-fiber stimulation was linked to lower current intensities required to induce pain (NRS 6: HS 3.6 vs. R 9.2 mA, p = 0.001) and resulted in larger axon reflex erythema for high stimulus intensities (AUCFlare: NRS 6, 320.7 vs. 234.1 cm2⋅min, p = 0.015; NRS 3, 79.1 vs. 51.0 cm2⋅min; p = 0.114). Preferential C-fiber stimulation indicated a correlation of axon-reflex erythema with the areas of secondary mechanical hyperalgesia (NRS 6: r = 0.21, p = 0.036; NRS 3: r = 0.48, p = 0.0016). In contrast, the mean area of secondary mechanical hyperalgesia did not differ between HS and R [AUCHyper: NRS 6, 1,555 (HS) vs. 1,585 cm2⋅min (R), p = 0.893; NRS 3, 590 (HS) vs. 449 cm2⋅min (R), p = 0.212] albeit it developed faster during HS. Our data confirm that silent nociceptors provoke the axon reflex erythema, but their role in secondary hyperalgesia appears to be less crucial.Clinical trial number: NCT0544026